Aplikasi Sarana Prasarana Pendidikan Pada SMKN 4 Kota Bengkulu Menggunakan Pemrograman Visual Basic - Yulianti, Liza; Prahasti, Prahasti; Sari, Venny Novita (UNIVED Press, 2020)
Poor management of educational facilities and infrastructure can cause various problems, especially in documenting and managing existing assets in schools. Educational infrastructure is a school asset that must be organized and managed well to support ensuring the quality of education at school. The use of information technology through programming languages ​​can create various applications according to user needs. This research aims to create educational facilities and infrastructure using the Visual Basic programming language and mySQL database. The system development method used is the Lift Cycle Development System (SDLC) OR the waterfall approach. The research stages start from system design, system analysis, system design, coding program, program testing, system implementation and system maintenance. The results of the research are the application of educational infrastructure with spatial data reports, infrastructure reports by type, infrastructure reports per space and recapitulation of educational infrastructure. The expected application is expected to be able to improve services for schools regarding information on educational facilities so that they can guarantee the quality of education at SMKN 4 Bengkulu City.